2018
DOI: 10.24200/sci.2018.4956.1007
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Solidification of Saturated Air in Two-Dimensional Stagnation Flow

Abstract: This study aims to investigate the stagnation-ow solidi cation of vapor from saturated air. Saturated air with strain rate a impinges on a at plate and, thus, condensation occurs and an icy layer forms on the plate because the plate temperature is below the freezing temperature of water. The ice surface was modeled as an accelerated at plate that moves toward the impinging uid. The unsteady Navier-Stokes equations were subjected to a similarity transformation to obtain a single ordinary di erential equation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…(15) The linearized system in Eqs. (13) with boundary conditions ( 14) is solved using the Chebyshev Spectral Collocation method [33][34][35]. The physical domain from 0 to 1 is rst converted into the nite domain of 0 to L. The value of L is chosen su ciently large.…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) The linearized system in Eqs. (13) with boundary conditions ( 14) is solved using the Chebyshev Spectral Collocation method [33][34][35]. The physical domain from 0 to 1 is rst converted into the nite domain of 0 to L. The value of L is chosen su ciently large.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Tayebi et al [33] analyzed free convection heat transfer in an annulus between confocal elliptic cylinders lled with CNT-water nano uid and found that the average Nusselt number was an increasing function of modi ed Rayleigh numbers. Abbasi and Ghayeni [34] studied saturated air water freezing in two-dimensional stagnation ow on a at plate. According to their study, below the start temperature of freezing, 10 C drop in substrate temperature causes a large increase in the ultimate thickness of the ice at fareld air temperature of 5 C, while it slightly increases the ultimate thickness of the ice at the air temperature of 20 C. Rana et al [35] considered hydrothermal characteristics of nano uid using KKL model with Brownian motion and recommended nano-uids as a better coolant than the base uid.…”
Section: Introductionmentioning
confidence: 99%